The Influence Of Apparatus' Work Attitudes On The Implementation Of The Legislation Functions Of Council Members In The Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Bone Bolango - Kidamu, Mohamad Rival; Sakir, Mochamad; Bakri, Bala; Dunggio, Swastiani (Program Studi Ilmu Pemerintahan, 2024)
This research aims to determine the magnitude of the influence of apparatus work attitudes on the implementation of the legislative function of council members at the Secretariat of the Regional People's Representative Council of Bone Bolango Regency. This research uses a quantitative approach with a survey method. The survey research in question is to explain causal relationships and test hypotheses. The number of samples in this study was 25 people. The data analysis method uses simple regression analysis. The results of the research show that the work attitude of the apparatus influences the implementation of the legislative function of council members at the Secretariat of the Regional People's Representative Council of Bone Bolango Regency. This means that the working attitude of the apparatus can support the implementation of the legislative function of council members.